2021
DOI: 10.1002/slct.202103359
|View full text |Cite
|
Sign up to set email alerts
|

A New Curcuminoids‐Coumarin Derivative: Mechanochemical Synthesis, Characterization and Evaluation of Its In Vitro Cytotoxicity and Antimicrobial Properties

Abstract: Over the years, several drugs have been developed deriving from plants to investigate possible therapeutic roles. Among them, curcuminoids and coumarins, which, display a wide range of biological activity against several strains. Therefore, it was synthesized a curcuminoids-coumarin derivative by a mechanochemical multicomponent reaction. By NMR and HRMS results confirmed the formation of a mixture of three curcuminoids-coumarin derivatives in the same sample. The Influence of time during the milling process w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(27 citation statements)
references
References 59 publications
0
27
0
Order By: Relevance
“…We should mention here the rare exception of a landmark study that investigated the possibility of polymorphs for MCRs derivatives [ 33 ]. After the synthesis of curcuminoid–coumarin derivatives by a MCR using mechanochemical conditions, a technique prone to creating polymorphs [ 34 , 35 , 36 ], authors concluded that no polymorph was noted for the product using different solvents or for the solventless conditions.…”
Section: “Melting Point-only” Characterization and Its Consequences T...mentioning
confidence: 99%
“…We should mention here the rare exception of a landmark study that investigated the possibility of polymorphs for MCRs derivatives [ 33 ]. After the synthesis of curcuminoid–coumarin derivatives by a MCR using mechanochemical conditions, a technique prone to creating polymorphs [ 34 , 35 , 36 ], authors concluded that no polymorph was noted for the product using different solvents or for the solventless conditions.…”
Section: “Melting Point-only” Characterization and Its Consequences T...mentioning
confidence: 99%
“…It is mostly cultivated in several tropical and subtropical regions around the world, and it originated in India, Southeast Asia and Indonesia. 10–12 Curcumin normally occurs together with other curcuminoids in turmeric rhizomes, such as demethoxycurcumin and bisdemethoxycurcumin. 10,11,13,14…”
Section: Introductionmentioning
confidence: 99%
“…10–12 Curcumin normally occurs together with other curcuminoids in turmeric rhizomes, such as demethoxycurcumin and bisdemethoxycurcumin. 10,11,13,14…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A variety of products and new heterocyclic systems were synthesized based on the reactivity of these coumarin derivatives towards various nucleophiles. They have shown numerous antimicrobial activities such as anticancer [8][9][10], antimicrobial [11,12], antibiotic [13], antiproliferative [14], anti-inflammatory [15], anticoagulant [16], antioxidant [17], and antibacterial [18],…”
Section: Introductionmentioning
confidence: 99%